FINANCIAL STATEMENT FRAUD DETECTION MENGGUNAKAN FRAUD HEXAGON THEORY PADA PERUSAHAAN DI JAKARTA ISLAMIC INDEX - Muhammad Arsad; Siti Amaroh; Bayu Tri Cahya (JURNAL ILMIAH EDUNOMIKA, 2024)
The research aims to analyze indications of fraud by using the fraud hexagon in companies registered on the Jakarta Islamic Index (JII) for 2019-2021. The sample selection technique uses a purposive sampling technique, the number of research samples is 14 companies. The research uses analytical techniques using e-views tools. The results of the study prove that: (1) external pressure which is proxied has a significant effect on the detection of fraudulent financial statements; (2) financial stability has a significant effect on the detection of financial statement fraud; (3) financial targets have a significant effect on the detection of fraudulent financial reporting; (4) change of directors (DCHANGE) has no significant effect on the detection of fraudulent financial reporting; (5) ineffective monitoring has no significant effect on the detection of fraudulent financial reporting; (6) the nature of industry has a significant effect on the detection of fraudulent financial reporting; (7) change of auditor (AUDCHANGE) has no significant effect on the detection of fraudulent financial statements; (8) the frequent number of CEO's picture (CEOPICT) has a significant effect on the detection of financial statement fraud; and (9) collusion (COL) has no significant effect on the detection of financial statement fraud. Keywords: Fraud Hexagon, External Pressure, Financial Stability